2020
DOI: 10.7150/thno.47066
|View full text |Cite
|
Sign up to set email alerts
|

Urinary glycoproteins associated with aggressive prostate cancer

Abstract: Background: There is an urgent need for the detection of aggressive prostate cancer. Glycoproteins play essential roles in cancer development, while urine is a noninvasive and easily obtainable biological fluid that contains secretory glycoproteins from the urogenital system. Therefore, here we aimed to identify urinary glycoproteins that are capable of differentiating aggressive from non-aggressive prostate cancer. Methods: Quantitative mass spectrometry data of glycopeptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 55 publications
3
36
0
Order By: Relevance
“…Normalization was performed on glycopeptides to the total protein amount in the individual urine sample. 16 Across 66 urine samples, 872 glycopeptides originating from 485 glycoproteins were identified and quantified with an FDR < 0.01 for both proteins and peptides ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normalization was performed on glycopeptides to the total protein amount in the individual urine sample. 16 Across 66 urine samples, 872 glycopeptides originating from 485 glycoproteins were identified and quantified with an FDR < 0.01 for both proteins and peptides ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…After the de- N -glycopeptides were identified and quantified, normalization was performed on the glycopeptide intensity to the total protein amount of the individual urine samples. 16 …”
Section: Materials and Methodsmentioning
confidence: 99%
“…For example, Vermassen et al showed that average total PSA urinary concentration (tPSA) before and after DRE was, respectively, 75.5 µg/L and 13,030 µg/L [ 48 ]. Dong et al analysed EPS-urines from 74 and 68 patients with AG PCa and NAG PCa, respectively; they aimed to detect differentially expressed glycoproteins among the two groups by data independent analysis (DIA) [ 49 ]. Briefly, the digestion of 500 µL of EPS-urine was performed by automated tryptic digestion on C4-tips (Lys-C 1 h and trypsin 6 h) [ 50 ]; after digestion, N-glycopeptides were isolated by automated C18/MAX-tip method followed by de-glycosylation with PNGase F and peptide purification by C18 StageTip [ 51 ].…”
Section: Glycoproteomics Of Biofluidsmentioning
confidence: 99%
“…From the general biological process, such as cell adhesion and signal transduction, to specific functions of proteins like folding and stability, the complexity imparted to a proteome by N- glycosylation is immense (Schjoldager et al, 2020 ). Moreover, the N- glycans biosynthesis process is very sensitive to the physiological and pathological states in cells (Mereiter et al, 2019 ; Dong et al, 2020 ), and glycoproteins are a main type of current therapeutic targets and disease biomarkers (Pan et al, 2020 ; Zhao et al, 2020 ). Fueled by the increasing discovery of disease-related N- glycans alterations, the interest in large-scale N -glycosylation profiling in clinical samples is proliferating.…”
Section: Introductionmentioning
confidence: 99%